Structural Basis of a Broadly Selective Acyltransferase from the Polyketide Synthase of Splenocin. (14th April 2018) - Li, Yuan; Zhang, Wan; Zhang, Hui; Tian, Wenya; Wu, Lian; Wang, Shuwen; Zheng, Mengmeng; Zhang, Jinru; Sun, Chenghai; Deng, Zixin; Sun, Yuhui; Qu, Xudong; et al.
Abstract: Polyketides are a large family of pharmaceutically important natural products, and the structural modification of their scaffolds is significant for drug development. Herein, we report high‐resolution X‐ray crystal structures of the broadly selective acyltransferase (AT) from the splenocin polyketide synthase (SpnD‐AT) in the apo form and in complex with benzylmalonyl and pentynylmalonyl extender unit mimics. These structures revealed the molecular basis for the stereoselectivity and substrate specificity of SpnD‐AT, and enabled the engineering of the industrially important Ery‐AT6 to broaden its substrate scope to include three new types of extender units.